2016
DOI: 10.5194/acp-16-3813-2016
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurements and modeling of reactive trace gases in a small biomass burning plume

Abstract: Abstract. An instrumented NASA P-3B aircraft was used for airborne sampling of trace gases in a plume that had emanated from a small forest understory fire in Georgia, USA. The plume was sampled at its origin to derive emission factors and followed ∼ 13.6 km downwind to observe chemical changes during the first hour of atmospheric aging. The P-3B payload included a proton-transfer-reaction timeof-flight mass spectrometer (PTR-ToF-MS), which measured non-methane organic gases (NMOGs) at unprecedented spatiotemp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
157
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(166 citation statements)
references
References 36 publications
9
157
0
Order By: Relevance
“…The increase in tropospheric ozone (O 3 ) in aged biomass burning plumes could last for days and even months (Thompson et al, 2001;Duncan et al, 2003;Real et al, 2007) with complex atmospheric chemistry (Arnold et al, 2015;Müller et al, 2016). Moreover, biomass and biofuel burning could contribute up to 70 % of the global secondary organic aerosol (SOA) burden (Shrivastava et al, 2015) and hence influence the seasonal variation of global SOA (Tsigaridis et al, 2014).…”
Section: Z Fang Et Al: Open Burning Of Rice Corn and Wheat Strawsmentioning
confidence: 99%
“…The increase in tropospheric ozone (O 3 ) in aged biomass burning plumes could last for days and even months (Thompson et al, 2001;Duncan et al, 2003;Real et al, 2007) with complex atmospheric chemistry (Arnold et al, 2015;Müller et al, 2016). Moreover, biomass and biofuel burning could contribute up to 70 % of the global secondary organic aerosol (SOA) burden (Shrivastava et al, 2015) and hence influence the seasonal variation of global SOA (Tsigaridis et al, 2014).…”
Section: Z Fang Et Al: Open Burning Of Rice Corn and Wheat Strawsmentioning
confidence: 99%
“…Several recent papers have reported the use of highresolution PTR-ToF to measure biomass burning NMOGs in the laboratory Bruns et al, 2017) and the environment (Brilli et al, 2014;Müller et al, 2016). Hatch et al (2017) suggest that PTR-ToF measures a substantial fraction (50-80 %) of total NMOG carbon mass.…”
mentioning
confidence: 99%
“…R. Koss et al: Non-methane organic gas emissions contribute to the formation of secondary pollutants including ozone and secondary organic aerosol (SOA; Alvarado et al, 2009Alvarado et al, , 2015Yokelson et al, 2009;Jaffe and Wigder, 2012). Because NMOGs from biomass burning are a complex mixture of many species that can change considerably depending on fuel and fire characteristics, many modeling and inventory efforts have had difficulty capturing subsequent chemistry in fire plumes (Alvarado et al, 2009;Grieshop et al, 2009;Wiedinmyer et al, 2011;Heald et al, 2011;Müller et al, 2016;Reddington et al, 2016;Shrivastava et al, 2017). Additionally, a substantial portion of gas-phase carbon may be missing from many field measurements (Warneke et al, 2011;Yokelson et al, 2013;Hatch et al, 2017) and the gas-phase precursors of SOA are not sufficiently understood (Jathar et al, 2014;Alvarado et al, 2015;Hatch et al, 2017).…”
mentioning
confidence: 99%
“…Many of these EFs are critically important to represent wildfire emissions well: e.g. NH 3 (Benedict et al, 2017) and SOA or PAN precursors (Alvarado et al, 2015;Müller et al, 2016 factorization was found to be a very useful method to predict field EF from the lab data for NMOG as discussed elsewhere (Sekimoto et al, in preparation). Finally, given the small amount of field sampling, more field work is clearly needed.…”
mentioning
confidence: 99%
“…To date, most of the research on the emissions and evolution of smoke from US fires has targeted prescribed fires (Burling et al, 2011;Akagi et al, 2013;May et al, 2014;Müller et al, 2016). However, wildfires burn a different mix of fuels in a different season that has more intense photochemistry and different smoke dispersion scenarios, and they typically consume more fuel per unit area than prescribed fires and can have different emission factors (EF, g compound 15 emitted/kg fuel burned ) (Campbell et al, 2007;Urbanski, 2013).…”
mentioning
confidence: 99%